Consumer confidence index influence on attitude towards sales promotion: comparison between Malaysia and Singapore - Tan, Yin Yin (Universiti Malaysia Sarawak, (UNIMAS), 2011)
(This study evaluates the impact of consumer confidence index towards sales promotion attitude in Malaysia and Singapore. The results of the data analysis show that different levels of consumer confidence index does not influence sales promotion attitude in Malaysia and Singapore; Nevertheless, at significance of 10% from the t-test analysis shows that different level of CCI does impact the attitude of Malaysia's consumer. In addition, low level of consumer confidence index shows difference when compared -between Malaysia and Singapore. Malaysia's mean score relatively is higher than Singapore. The study provides insights through incorporating consumer confidence index and sales promotion attitude between Malaysia and Singapore based on the attitude formation process, the CAB Paradigm. Hence the study will lead to further expansion in research in the future.